AGROTEKNOLOGI KOPI GRAFTING UNTUK PENINGKATAN PRODUKSI - Rusdi Evizal; Fembriarti Erry Prasmatiwi (Jurnal Agrotek Tropika, 2020)
Lampung Province is the center of Robusta coffee production with an area of 2018 reaching 157.6 thousand hectares while Arabica coffee which has been programmed in 1998 by planting area reached 1.9 thousand hectares did not develop successfully even disappearing. Liberica coffee is commonly grown as a rootstock. This research aims to study the ethno-agronomy of various grafting coffees in Lampung, both Robusta- Liberica and Arabica-Robusta. This research was carried out using Focus Group Discussion (FGD) method with the farmer groups and the observation of coffee plantations in the field belonging to group members in each farmer group selected purposively in each district namely Sekincau Sub-district of West Lampung, Sumberejo Sub-district of Tanggamus, and Way Ratai Sub-district of Pesawaran, in May-October 2019. The results showed that farmers developed a various of intraspecific coffee grafting (Robusta/Robusta) using a variety of superior local clones and interspecific grafting (Robusta/Liberica and Arabica/Robusta) with specific agronomy practices such as cloning, planting, pruning, fertilizing, applying pesticide, soil conserving, and being non-resident farmers as creations, local wisdom and adaptation of farmers to site-specific conditions. Keywords : Clone, ethno-agronomy, fertilizing, interspesific grafting, local wisdom, rainfall